The Encyclical-Letter “Caritas in Veritate”: Ethical Challenges for Business - Melé Carné, Domènec; Naughton, Michael C. (2011)
This article serves as an editorial introduction to this special issue on Pope Benedict’s encyclical-letter, Caritas in Veritate (2009) and its engagement with the field of business ethics. According to this document, love in truth, which includes justice, is indeed presented as a basic moral foundation for economic and business ethics. The article provides an overview of some major themes in the encyclical and their relationship to the essays in this special issue. The authors in this issue are an interdisciplinary group of scholars in the fields of philosophy, theology, psychology, business, economics, and political science who address the relevance and relationship of the encyclical to business ethics in light of their disciplinary field. Their articles include, among other topics, discussions based on recent scholarship on business ethics, the economics and ethics relationship, the orientation of business to the common good, the encyclical’s proposal of the principle of gratuitousness and the logic of gift in ordinary business, and new perspectives on economic exchange and bargains and hybrid forms of business.
Keywords: New forms of business; Economic and ethics relationship; Principle of gratuitousness; Love in truth; Logic of gift; Common Good; Caritas in Veritate; Business Ethics; Benedict XVI; Agape